Frequencies of drought at Ranchi regions, Jharkhand - SINGH, P. K.; RATHORE, L. S.; ATHIYAMAN, B.; SINGH, K. K.; BAXLA, A. K.; KUMAR , ASHOK; BHARGAVA, A. K. (MAUSAM, 2009)
Studies of water balance have been carried out for Ranchi taking 35 years (1970-2004) of climate data. Ranchi has annual water need of 1754 mm, rainfall of 1460 mm, actual evapotranspiration (AE) of 860 mm, water surplus (WS) of 600 mm and water deficit (WD) of 894 mm. The aridity index values were analyzed to assess the frequency of drought experienced of this region. The study reveals that during the above period, Ranchi has experienced 11 percent of large drought and severe drought, but only 3 per cent disastrous droughts in 35 years. Moderate drought category is observed to be most common with 23 per cent probability. Analyses of periods will contagious drought indicate that during the five year period 1980-84 and 1995-99, moderate, large and severe droughts were experienced.